Use of Low Enriched Uranium Fuel in Accelerator Driven Subcritical Systems. - IAEA (IAEA TECDOC Series No. 1821., 2017)
"This publication presents the results and conclusions of an international research collaboration devoted to gaining a better understanding of the physics of Accelerator Driven Subcritical Systems (ADS), with particular emphasis on using low enriched uranium (LEU) fuel. The publication contains information on nine ADS facilities, including descriptions of the hardware deployed, experiments conducted, computational resources and procedures used in the analyses, principal results obtained, and conclusions drawn from the knowledge gained as a consequence of this work. It is intended to provide information for users of ADS systems and those involved in the design of new ADS facilities to use LEU fuel and in the conversion of some existing facilities from using highly enriched Uranium (HEU) to LEU."--Publisher's description.